2012
DOI: 10.1002/macp.201100661
|View full text |Cite
|
Sign up to set email alerts
|

Hexahapto‐Metal Complexes of Single‐Walled Carbon Nanotubes

Abstract: We report the preparation of organometallic side‐wall complexes of single‐walled carbon nanotubes (SWNTs) under conditions, which allow the study of both mono‐ and bis‐hexahapto SWNT coordination compounds [(η6‐SWNT)Cr(CO)3, (η6‐SWNT)Cr(η6‐C6H6), (η6‐SWNT)2Cr]. The results are interpreted in terms of exohedral and endohedral binding of chromium to the SWNT sidewalls and ligand competition reactions suggest that endohedral binding provides a very stable and kinetically inert mode of organometallic bonding. We d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
90
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(101 citation statements)
references
References 105 publications
9
90
2
Order By: Relevance
“…These systems are also experimentally relevant. 27 Larger decreases in the transmission function are observed in our results if there is only a Cr atom without a benzene molecule attached to a carbon ring of the nanotube. Thus, high concentrations of especially adsorbed (and possibly oxidized) Cr atoms should be avoided, e.g., by sputtering the Cr treated CNT networks.…”
Section: Introductionsupporting
confidence: 43%
See 1 more Smart Citation
“…These systems are also experimentally relevant. 27 Larger decreases in the transmission function are observed in our results if there is only a Cr atom without a benzene molecule attached to a carbon ring of the nanotube. Thus, high concentrations of especially adsorbed (and possibly oxidized) Cr atoms should be avoided, e.g., by sputtering the Cr treated CNT networks.…”
Section: Introductionsupporting
confidence: 43%
“…26 Experimentally, it has been shown that transition metal (TM) atoms reduce the junction resistance efficiently. 27,28 In particular, chromium linker atoms enhance the conductance of the junction significantly. Group 6 TM atoms chromium, molybdenum, and tungsten possess six valence electrons and these atoms obtain a closed-shell structure when they bind to two carbon sidewall hexagons in CNT junctions.…”
Section: Introductionmentioning
confidence: 99%
“…Films of their Cr(SCWNT) 2 sandwich complex were observed to have an increase in C 2017, 3, 17 2 of 15 conductivity of over 100% [5]. They also reported conductivity increases for tungsten and molybdenum sandwich complexes synthesized by the same method [7].…”
Section: Introductionmentioning
confidence: 89%
“…In concept, this is an extension of doping studies where metal and non-metal species are known to intercalate within CNT bundles [5]. As part of their work, it was reported that the "Cr(CO) 3 " moiety could be coordinated to both the graphene surface and also the sidewalls of SWCNTs [5,7]. Films of their Cr(SCWNT) 2 sandwich complex were observed to have an increase in C 2017, 3, 17 2 of 15 conductivity of over 100% [5].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation